Discovering Inclusive Education Through the Voices of Students in Priority Education Intervention Territories (TEIP) (Revista Lusófona de Educação, 2025)
Within the framework of inclusive education, Portugal has developed measures to reduce socio-economic and geographical asymmetries, namely the Educational Territories of Priority Intervention (TEIP) program, whose monitoring must include the active voice of the main stakeholders and include students. However, there is little evidence of the student voice in TEIP schools. In this study, the aim was to analyze the perception of students in TEIP programs about: 1) inclusive education, 2) the inclusive practices of teachers, 3) the inclusive school environment and 4) how this perception evolves throughout their academic career, analyzing the following variables: gender, educational support and retention. To this end, 637 students from TEIP schools, aged between 6 and 18, 319 females and 318 males, answered the questionnaire Students’ perceptions of inclusive education. The results indicate that students positively evaluate the schools’ initiatives in favor of inclusion, although they point out the need for teachers to consult students more on how to improve the classroom environment. The positive perception of inclusive education is general among students, with no significant differences between girls and boys. However, there is room for improvement in teaching practices and research.Keywords: Inclusive Education; TEIP Schools; Student Voice.